2009
DOI: 10.1523/jneurosci.1350-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Awake Intranasal Insulin Delivery Modifies Protein Complexes and Alters Memory, Anxiety, and Olfactory Behaviors

Abstract: The role of insulin pathways in olfaction is of significant interest with the widespread pathology of diabetes mellitus and its associated metabolic and neuronal comorbidities. The insulin receptor (IR) kinase is expressed at high levels in the olfactory bulb, in which it suppresses a dominant Shaker ion channel (Kv1.3) via tyrosine phosphorylation of critical N-and C-terminal residues. We optimized a 7 d intranasal insulin delivery (IND) in awake mice to ascertain the biochemical and behavioral effects of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
224
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(236 citation statements)
references
References 82 publications
10
224
0
2
Order By: Relevance
“…However, we observed an antidepressant effect in the FST at an IN D1-D2 interfering peptide dose of X1.67 nmol/g, B100-fold larger than that given directly to the prefrontal cortex (5 nmol per injection) in our previous study (Pei et al, 2010). We chose this starting dose based on previous studies of IN administration of small proteins such as NGF and insulin to the CNS that indicated that the efficiency of delivery to the CNS is between 1 and 5% (De Rosa et al, 2005;Dhuria et al, 2010;Francis et al, 2008;Marks et al, 2009). Although the proportion of the original IN dose of the D1-D2 interfering peptide present in the PFC after IN administration remains unknown, our results suggest that the efficiency of delivery to the CNS after IN administration using the POD device is at least 1-5%.…”
Section: Discussionmentioning
confidence: 94%
“…However, we observed an antidepressant effect in the FST at an IN D1-D2 interfering peptide dose of X1.67 nmol/g, B100-fold larger than that given directly to the prefrontal cortex (5 nmol per injection) in our previous study (Pei et al, 2010). We chose this starting dose based on previous studies of IN administration of small proteins such as NGF and insulin to the CNS that indicated that the efficiency of delivery to the CNS is between 1 and 5% (De Rosa et al, 2005;Dhuria et al, 2010;Francis et al, 2008;Marks et al, 2009). Although the proportion of the original IN dose of the D1-D2 interfering peptide present in the PFC after IN administration remains unknown, our results suggest that the efficiency of delivery to the CNS after IN administration using the POD device is at least 1-5%.…”
Section: Discussionmentioning
confidence: 94%
“…12,13 Orexogenic hormones tended to increase and anorexogenic hormones tended to decrease olfactory sensitivity, modulating olfactory performance in a similar way as fasting and satiation. 12 Insulin, when administered intranasally to mice, leads to greater difficulty in discriminating two odors, 14 but there was a trend toward decreased odor threshold. However, intranasal insulin was administered over several days before testing odor thresholds, therefore rather reflecting chronic hyperinsulinemia in the brain than an acute response to food intake.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, mice were kept in supine position for 1 min to ensure that nasal gel was inhaled. This drug delivery process was repeated daily through the other nostril alternately (Marks et al, 2009). To evaluate the effect of nasal gel HupA on APP/PS1 mouse brain, mice at the age of 10 months were anaesthetized with sodium pentobarbital (50 mg/kg, i.p.)…”
Section: Preparation Of Nasal Gel Containing Hupa and Administration mentioning
confidence: 99%